LOGISTICAL ASPECTS OF THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN THE PRINTING INDUSTRY (International Journal of Management Trends: Key Concepts and Research, 2025)
This paper explores the potential application of artificial intelligence (AI) and expert systems (ES) in improving logistics processes within the printing industry, with a particular focus on small and medium-sized enterprises (SMEs). The study is based on a case analysis of the printing company SITOPRINT from Žitište, which represents a typical SME operating with a combination of traditional and modern printing technologies, yet facing evident logistical constraints. The primary objective of the research is to identify key logistical limitations, assess the level of digital maturity, and determine the extent to which AI-based solutions can enhance operational stability, efficiency, and cost-effectiveness.The methodological framework includes the analysis of internal business documentation, direct observation of workflow, interviews with employees, and evaluation of existing procedures related to material management, production planning, and distribution. Additionally, a comparative review of modern logistics solutions in international practice was conducted to contextualize global trends in industrial digitalization and assess their applicability to the Serbian printing sector.Findings indicate that SITOPRINT’s logistics processes rely heavily on manual work, fragmented communication, and experience-based decision-making, resulting in inventory fluctuations, uneven machine utilization, and reduced predictability. The research shows that AI can significantly improve these processes through predictive inventory management, automated production scheduling, real-time order tracking, and algorithm-based route optimization.The discussion emphasizes that the successful implementation of AI and ES requires gradual integration, employee training, and the development of a data-driven organizational culture. The conclusion highlights that AI-supported logistics represents a sustainable and scalable development path for SMEs in the printing industry, and that the SITOPRINT case may serve as a practical model for broader industry modernization.